2021
DOI: 10.3847/1538-4357/abd7a0
|View full text |Cite
|
Sign up to set email alerts
|

Inferred Linear Stability of Parker Solar Probe Observations Using One- and Two-component Proton Distributions

Abstract: The hot and diffuse nature of the Sun’s extended atmosphere allows it to persist in non-equilibrium states for long enough that wave–particle instabilities can arise and modify the evolution of the expanding solar wind. Determining which instabilities arise, and how significant a role they play in governing the dynamics of the solar wind, has been a decades-long process involving in situ observations at a variety of radial distances. With new measurements from the Parker Solar Probe (PSP), we can study what wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 24 publications
1
47
0
Order By: Relevance
“…Most recent studies have led to a paradigm shift whereby the proton multiple populations and beams are born out of wave-particle interactions (of various types) and turbulence (e.g., Montgomery et al 1976;Livi & Marsch 1987;Gary 1991;Daughton & Gary 1998;Daughton et al 1999;Tam & Chang 1999;Tu et al 2002Tu et al , 2004Araneda et al 2008;Matteini et al 2010;Osmane et al 2010;Pierrard & Voitenko 2010;Valentini et al 2011;Voitenko & Pierrard 2015;Alterman 2019). Many studies also focused on the instabilities that result from the presence of the beam, and on their effects back on the proton distributions themselves (e.g., Wong & Goldstein 1988;Gomberoff 2006;Matteini et al 2010Matteini et al , 2015Hellinger & Trávníček 2011Chen et al 2016;Wicks et al 2016;Verscharen et al 2016;Shaaban et al 2020;Klein et al 2021;Louarn et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Most recent studies have led to a paradigm shift whereby the proton multiple populations and beams are born out of wave-particle interactions (of various types) and turbulence (e.g., Montgomery et al 1976;Livi & Marsch 1987;Gary 1991;Daughton & Gary 1998;Daughton et al 1999;Tam & Chang 1999;Tu et al 2002Tu et al , 2004Araneda et al 2008;Matteini et al 2010;Osmane et al 2010;Pierrard & Voitenko 2010;Valentini et al 2011;Voitenko & Pierrard 2015;Alterman 2019). Many studies also focused on the instabilities that result from the presence of the beam, and on their effects back on the proton distributions themselves (e.g., Wong & Goldstein 1988;Gomberoff 2006;Matteini et al 2010Matteini et al , 2015Hellinger & Trávníček 2011Chen et al 2016;Wicks et al 2016;Verscharen et al 2016;Shaaban et al 2020;Klein et al 2021;Louarn et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The secondary proton beam population in VDFs has now been recognized to play as significant role in energy transfer in the inner heliosphere as the core proton population. Joint observations by PSP's Solar Wind Electrons Alphas and Protons (SWEAP) (Kasper et al 2016) and FIELDS (Bale et al 2016) instrument suites show the presence of ubiquitous proton beams concurrent with ion-scale waves (Bale et al 2019;Bowen et al 2020a;Verniero et al 2020;Klein et al 2021). PSP's first perihelion encounter with the Sun revealed a diversity of stream characteristics in the near-Sun solar wind, including large-amplitude Alfvénic "switchbacks" and intervening "quiescent" periods of nearradial magnetic field (Bale et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Zhao et al (2019) identified the interplay of the proton beam and proton temperature anisotropy on the proton instability, and they provided an observational evidence of the proton instability enhanced by the proton beam. Recently, Klein et al (2021) used two popular models (a single anisotropic population and two relatively drifting anisotropic populations) to fit the proton phase-space densities in two ion-scale wave activity events observed by PSP, and they found that the two-component model can result in the instability much stronger than the one-component model.…”
Section: Observational Evidences Of the Proton Beam Instabilitymentioning
confidence: 99%
“…Bowen et al (2020) showed that ion-scale waves are observed 30% − 50% radial field intervals in the first encounter of PSP. Moreover, in comparison to the proton beam speed comparable to V A in the solar wind nearby 1 au, proton beams are at times seen by PSP with relative speeds 1.5V A (Klein et al 2021). Since PSP will measure the ion velocity distribution and electromagnetic fields down to the heliocentric distance at 9.8R s , it provides a unique opportunity to identify the excitation of the proton beam instability in the solar atmosphere.…”
Section: Introductionmentioning
confidence: 99%